Sleep disturbance and problematic alcohol use: Examination of sex and race differences - Dzierzewski, Joseph M.; Ravyts, Scott G.; Martin, Caitlin E.; Polak, Kathryn M.; Nielson, Spencer A.; Pomm, David; Dillon, Pamela; Moore, Thomas B.; Thacker, Leroy R.; Svikis, Dace S. (Frontiers in Sleep, 2022)
Objectives: Disrupted sleep is prevalent and related to problematic alcohol use. While sex and race disparities exist in both sleep disturbances and problematic alcohol use, whether the association between disrupted sleep and problematic alcohol use is similar across sex and race is unknown. The present study sought to examine sex and race invariance in the association between disrupted sleep and problematic alcohol use. Methods: Secondary analyses of baseline data from a randomized clinical trial targeting heavy drinking in primary care facilities. Participants completed four individual sleep questions (sleep quality, difficulty falling asleep, difficulty staying asleep, and sleep medication use), along with sex-specific measures of problematic alcohol use (i.e., CAGE and T-ACE). A structural equation model (SEM) was used to examine the association between a latent sleep disturbance construct and problematic alcohol use, as well as potential sex and race invariance of this association. Results: Participants included 1,448 adults (76.59% female, 76.73% Black, Mage=44.78, SD=12.35). The majority of the sample reported one or more sleep disturbance symptoms and 31.84% of participants screened positive for problematic alcohol use. Greater sleep disturbance was significantly associated with a greater risk of problematic alcohol use (β=.18, p<.001), and did not differ by either sex or race. Conclusions: Disrupted sleep is associated with problematic alcohol use, across sex and race. Sleep interventions may hold promise as treatment augments in individuals with problematic alcohol use.